Guillain-Barré Syndrome in Pregnancy. Issue 2 (June 2017) - Pacheco, L.D.; Saad, A.F.; Hankins, G.D.; Chiosi, G.; Saade, G.
Abstract : ( Obstet Gynecol . 2016;128(5):1105–1110) Guillain-Barré syndrome is defined as a progressive neurological disease that causes the acute onset of symmetric ascending motor weakness, which at times results in respiratory failure and autonomic dysfunction. When this syndrome occurs during pregnancy it has been associated with increased maternal mortality (10%). In addition, over 35% of the affected pregnant women with this disorder require respiratory support. Recent reports have noted an association between Guillain-Barré syndrome and infection with the Zika virus in pregnant women. This report reviewed the autoimmune nature of the syndrome and described its clinical characteristics in addition to providing up-to-date evidence for the diagnosis and management of the disease, especially during pregnancy.